Measurement of the time-integrated CP asymmetry in D0 → K0SK0S decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Journal of high energy physics, 2015)
The time-integrated CP asymmetry in the decay D0 → KS0KS0is measured using 3 fb−1 of proton-proton collision data collected by the LHCb experiment at centre-of-mass energies of 7 and 8 TeV. The flavour of the D0 meson is determined by use of the decay D*+ → D0π+ and its charge conjugate mode. The result isACP=−0.029±0.052±0.022, where the first uncertainty is statistical and the second systematic. The result is consistent with Standard Model expectations and improves the uncertainty with respect to the only previous measurement of this quantity by more than a factor of three.
Im Titel ist "0" hochgestellt, "S" ist tiefgestellt, dabei steht "S" unter "0"
The LHCb Collaboration: R. Aaij, B. Adeva; M. Adinolfi, O. Aquines Gutierrez, P. d'Argent, S. Bachmann, A. Bien, J. Blouw, M. Britsch, S. Braun, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, J. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Schmelling, M. Stahl, U. Uwer, M. Vesterinen, C. Voß, R. Waldi, S. Wandernoth, A. Zhelezov [und 686 weitere]
Gesehen am 07.04.2021